PENGARUH RETENSI NADHOMAN TERHADAP PENINGKATAN PRESTASI SANTRI DALAM PEMBELAJARAN KITAB ALFIYAH IBN MALIK DI PONDOK PESANTREN NGALAH PURWOSARI - Febrianti, Firda Cahyaning; Abdullah, Muhammad; Ma'ruf, Ahmad; Yusuf, Achmad (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2023)
The Ngalah Purwosari Islamic Boarding School is one of the Ngalah Islamic Boarding Schools that requires students to memorize nadhom nahwu science at the wustho level. The purpose of this study was to determine the effect of nadhoman retention on increasing achievement in learning the book of alfiyah ibn malik at the Ngalah Purwosari Islamic Boarding School, and to determine the relationship of nadhoman retention to increasing achievement in learning the book of alfiyah ibn malik at the Ngalah Purwosari Islamic Boarding School. This research uses quantitative research methods. This study used 45 respondents of wustho santriwati as research subjects. Based on the validity test and reliability test on the knowledge variable questions, 20 valid questions were obtained with a correlation value of more than 0.294. The validity test on the question list is declared valid because all have met the criteria. In the reliability test of the variables of knowledge, attitudes and behavior, realistic or consistent results were obtained because each of the reliability tests obtained a coefficient value of 0.724. An r value of 0.876 is given for the hypothesis testing phase based on correlation testing. It is in the range of 0.70 to 0.90, so we can say that it is related. This means that the degree of relationship between the two variables is very high, and since the significance test shows values of 0.00 < 0.05, it can be said that a hypothesis test with the label "There is a relationship between pre-test and post-test" is acceptable.